Analisis Permintaan Uang Giral dalam Valuta Asing Tahun 2000-2002: Studi Kasus Kabupaten/Kota di Propinsi Daerah Istimewa Yogyakarta, Jawa Tengah, Jawa Timur, dan Jawa Barat - Suripto Suripto (Economic Journal of Emerging Markets, 2006)
This research investigated demand for demand deposit in foreign exchange. Data used was panel data, which is combination from time series data and cross sectional data.Estimation method used was generalized least square (GLS) with polled regression, fixed effect (Covariance model) and random effect (Error model) models. Based on restricted F test and Lagrange Multiplier test (LM test), it is known that fixed effect model is the best model to explain demand for demand deposit in foreign exchange. It means that element of region (regency/municipality) effects model structure. Least Square Dummy Variable (LSDV) regression model by incorporating time element indicates that local autonomy event did not influence model structure. It is supported with Chow test indicating that the model is stable due to enforcement of Law No 22 and 25 of 1999.Keys Word: demand deposits in foreign exchange, panel data, fixed effect model